Student Perceptions of Teacher-Written Feedback on their Writing in an IELTS Exam Preparation Class: Implications for Teaching Writing for IELTS - Donaghue, Edward (2018)
Teacher feedback is considered a key component in the process of teaching academic writing, but the nature of effective feedback and the extent to which it improves student writing has long been the subject of debate. There is a large body of research concerned with effective feedback, but less attention has been paid to how students actually perceive and use teacher feedback (Evans, 2013). This small-scale study aimed to identify features of effective feedback by investigating changes in perceptions of teacher-written feedback in a group of 12 students on an IELTS exam preparation course. The study used qualitative and quantitative data from focus group interviews and questionnaires to examine changes in student perceptions over a 12-week semester. It also analysed student essays to examine whether changes in student perceptions were reflected in improvement in student writing. From the analysis of qualitative and quantitative data, student perceptions of useful feedback were identified: feedback was effective when it provided information about current performance levels and also challenged, motivated and fed forward to future writing tasks by relating to ideal standards. This corroborates the findings of Hattie and Timperley (2007). From the analysis of student essays, an interactive approach to written feedback which may be effective in the development of reader-based and criterion-based writing for IELTS was also identified. Two main findings emerged in relation to feedback on academic writing: feedback on academic writing is part of a process of scaffolding writing skills and students need to use it formatively to improve future writing. However, feedback alone is not sufficient to improve student writing: it needs to form part of a wider process of scaffolding which takes account of factors related to the learner and the learning context.